Nglanggeran village: a model for sustainable tourism through multi-stakeholder engagement and corporate social responsibility - Hendrayani, Yani; Zen, Irina Safitri; Uljanatunnisa, Uljanatunnisa; Maryam, Siti (Sage Publications, 2025)
The rapid transformation of Nglanggeran, an Indonesian rural village, from poor to globally popular demonstrates how multi-stakeholder collaborations and strategic corporate social responsibility (CSR) drive sustainable tourism. This case study explored how developing a comprehensive CSR program led by Bank Indonesia, the Central Bank, helped Nglanggeran overcome its economic and environmental challenges and emerge as a global leader in community-based tourism. Selin and Chavez’s tourism partnership model, alongside the CSR framework; a strategic “cluster management and zone assessment,” and the community’s social capital were used to investigate a tourism initiative’s development in Nglanggeran. An intrinsic case study, observations, semi-structured and in-depth interviews, and content analysis were used to explore multi-stakeholder collaboration and CSR initiative implementation targeting sustainable village tourism. The CSR program, which was more than philanthropic, was crucial in Nglanggeran’s success. Moreover, active participation and synergistic contributions of diverse stakeholders, each providing unique assets and expertise, were important for Nglanggeran’s transformation. This study provides a promising model for local and international rural communities, demonstrating how strategic CSR initiatives and collaborative approaches favor sustainable tourism in villages via multi-stakeholder collaboration, involving private sectors, local governments, academia, and communities. Further research should explore collaboration dynamics in CSR practices and integrate emerging technologies (e.g., virtual reality and artificial intelligence) to better promote and manage sustainable tourism villages. Bank Indonesia’s CSR program could identify the village’s unique strengths and tailor interventions accordingly. This included facilitating the development of a thriving cocoa-based tourism product closely aligned with the local environment and expertise.